Withering Hegemony of US and Evolving De-centered Globalism: A Theoretical account - Liu Debin♣ Rizwan Naseer Musarat Amin (Journal of Political Studies, 2012)
In this essay theoretical description has been applied to explicate that the days of American Unilateralism are gone and now the other potential actors are catching up with American supremacy. American hegemony declared by advocates of hegemonic stability theory as indispensable for stable and prosperous world doesn’t hold water anymore. Balance of power theory explains the balancing behavior triggered off by other rising powers when their interests are threatened by a single superpower. Power transition theory sounds out that now power is gradually shifting from West to East.